The mutation DGT1-1 decreases glucose transport and alleviates carbon catabolite repression in Saccharomyces cerevisiae. - Gamo, F J (1994)
Glucose in ethanol-glycerol mixtures inhibits growth of Saccharomyces cerevisiae mutants lacking phosphoglycerate mutase. A suppressor mutation that relieved glucose inhibition was isolated. This mutation, DGT1-1 (decreasing glucose transport), was dominant and produced pleiotropic effects even in an otherwise wild-type background. Growth of the DGT1-1 mutant in glucose was dependent on respiration, and no ethanol was detected in the medium within 7 h of glucose addition. When grown on glucose, the mutant had a reduced glucose uptake and both the low- and high-affinity transport systems were affected. In galactose-grown cells, only the high-affinity glucose transport system was detected. This system had similar kinetic characteristics in the wild type and in the mutant. Catabolite repression of several enzymes was absent in the mutant during growth in glucose but not during growth in galactose. In contrast with the wild type, the mutant grown in glucose had high transcription of the glucose transporter gene SNF3 and no transcription of HXT1 and HXT3. Expression of multicopy plasmids carrying the HXT1, HXT2, or HXT3 gene allowed partial recovery of both fermentative capacity and catabolite repression in the mutant. The results suggest that DGT1 codes for a regulator of the expression of glucose transport genes. They also suggest that glucose flux might determine the levels of molecules implicated as signals in catbolite repression.